23Na magnetic resonance imaging-determined tissue sodium in healthy subjects and hypertensive patients - Kopp, Christoph; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Mueller, Dominik N.; Schmieder, Roland; Cavallaro, Alexander Josef; Eckardt, Kai-Uwe; Uder, Michael; Luft, Friedrich C.; Titze, Jens (Hypertension, 2013)
High dietary salt intake is associated with hypertension; the prevalence of salt-sensitive hypertension increases with age. We hypothesized that tissue Na might accumulate in hypertensive patients and that aging might be accompanied by Na deposition in tissue. We implemented Na magnetic resonance imaging to measure Na content of soft tissues in vivo earlier, but had not studied essential hypertension. We report on a cohort of 56 healthy control men and women, and 57 men and women with essential hypertension. The ages ranged from 22 to 90 years. Na magnetic resonance imaging measurements were made at the level of the calf. We observed age-dependent increases in Na content in muscle in men, whereas muscle Na content did not change with age in women. We estimated water content with conventional MRI and found no age-related increases in muscle water in men, despite remarkable Na accumulation, indicating water-free Na storage in muscle. With increasing age, there was Na deposition in the skin in both women and men; however, skin Na content remained lower in women. Similarly, this sex difference was found in skin water content, which was lower in women than in men. In contrast to muscle, increasing Na content was paralleled with increasing skin water content. When controlled for age, we found that patients with refractory hypertension had increased tissue Na content, compared with normotensive controls. These observations suggest that Na magnetic resonance imaging could have utility in assessing the role of tissue Na storage for cardiovascular morbidity and mortality in longitudinal studies. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aging; gender difference; hypertension; salt; sodium MRI